Maprotiline Prevents Monocrotaline-Induced Pulmonary Arterial Hypertension in Rats - Tong, Yi; Jiao, Qian; Liu, Yuanru; Lv, Jiankun; Wang, Rui; Zhu, Lili (Frontiers in Pharmacology, 2018)
Pulmonary arterial hypertension (PAH) is a progressive disease caused by increased pulmonary artery pressure and pulmonary vascular resistance, eventually leading to right heart failure until death. Soluble guanylate cyclase (sGC) has been regarded as an attractive drug target in treating PAH. In this study, we discovered that maprotiline, a tetracyclic antidepressant, bound to the full-length recombinant sGC with a high affinity (KD = 0.307 μM). Further study demonstrated that maprotiline concentration-dependently inhibited the proliferation of hypoxia-induced human pulmonary artery smooth muscle cells. Moreover, in a monocrotaline (MCT) rat model of PAH, maprotiline (ip, 10 mg/kg once daily) reduced pulmonary hypertension, inhibited the development of right ventricular hypertrophy and pathological changes of the pulmonary vascular remodeling. Taken together, our studies showed that maprotiline may contribute to attenuate disease progression of pulmonary hypertension.